Energy Distribution Characteristics and Environmental Impact Factors in Different Regions of the Summer Monsoon Transition Zone - Ren, Xueyuan; Zhang, Qiang; Yue, Ping; Yan, Xinyang; Yang, Yang (Frontiers in Environmental Science, 2022)
The summer monsoon transitional zone is a typical transitional ecosystem that is, also ecologically fragile. It is critical to explore the land surface energy balance and the water and heat transfer processes in this region for water resource management. However, the processes of surface water and heat transfer throughout the transition zone and the effects of environmental factors on energy distribution are understudied. Therefore, we analyzed the surface energy distribution and the environmental factors influencing it in the eastern and western transition zone from July to September, and compared the differing effects of meteorological factors and vegetation on the energy distribution between the two regions. The results show that the main consumption item of the available energy in the west of the transition zone is the latent heat flux. The same is true in the eastern region from July to August, but it changes to sensible heat flux in September. The factors influencing the Bowen ratio in the two regions were ground temperature difference, vapor pressure deficit, shallow soil water content, and drought stress index. Nevertheless, the Bowen ratio in the western region was more sensitive to water factors, whereas that in the eastern region was more sensitive to energy factors. The relationship between the Bowen ratio and the normalized difference vegetation index in the eastern region was more regular. This study provides a scientific basis for reasonably guiding agricultural production in the transition area.